Atomic-level architecture and assembly mechanism of high-order structures of RIPK1 fibril revealed by integrated structural biology - Jing Liu; An Mu; Shaojie Ma; Yi Liu; Jing Zhang; Jun-zhuo Zhao; Jian Wang; Xia-lian Wu; Jun-xia Lu (Proceedings of the National Academy of Sciences, 2026)
Receptor-interacting serine/threonine-protein kinase 1 (RIPK1) regulates cell death pathways through RHIM domain–mediated amyloid fibril formation. While amyloid fibrils typically exist as single filaments, we identified a higher-order architecture—the mouse RIPK1 (mRIPK1) fibril network—formed by the self-assembly of mRIPK1 fibrils into quadrilateral/hexagonal lattices under slightly acidic conditions. Using an integrative approach combining solid-state NMR, transmission electron microscopy, atomic force microscopy, X-ray diffraction, Cryo–electron tomography, and molecular dynamics simulations, we elucidated the atomic structure and assembly mechanism of this network. In this study, solid-state NMR analysis demonstrates that the mRIPK1 fibril core adopts an N-shaped parallel β-sheet conformation, with dynamic regions flanking the fibril core that likely participate in network formation. We propose that the electrostatic interactions between fibril core edge residues D516-K519 or D537-K519 are essential for the network formation, with proper positioning and exposure for interaction determined by the fibril structure and the length of the dynamic flexible domain, particularly the periodic twist of the fibril. Site-directed mutagenesis confirms the critical role of these edge residues in maintaining network integrity. This study presents an atomic model of a higher-order assembly formed by naturally occurring amyloid fibrils, offers fundamental insights into hierarchical fibril assembly, and establishes a framework for designing engineered amyloid-based materials.